Evolutionary genomics of Leishmania braziliensis across the neotropical realm - Senne Heeren; Mandy Sanders; Jeffrey Jon Shaw; Sinval Pinto Brandão-Filho; Mariana Côrtes Boité; Lilian Motta Cantanhêde; Khaled Chourabi; Ilse Maes; Alejandro Llanos-Cuentas; Jorge Arevalo; Jorge D. Marco; Philippe Lemey; et al. (Communications Biology)
Abstract The Neotropical realm, one of the most biodiverse regions on Earth, houses a broad range of zoonoses that pose serious public health threats. Protozoan parasites of the Leishmania (Viannia) braziliensis clade cause zoonotic leishmaniasis in Latin America with clinical symptoms ranging from simple cutaneous to destructive, disfiguring mucosal lesions. We present the first comprehensive genome-wide continental study including 257 cultivated isolates representing most of the geographical distribution of this major human pathogen. The L. braziliensis clade is genetically highly heterogeneous, consisting of divergent parasite groups that are associated with different environments and vary greatly in diversity. Apart from several small ecologically isolated groups with little diversity, our sampling identifies two major parasite groups, one associated with the Amazon and the other with the Atlantic Forest biomes. These groups show different recombination histories, as suggested by high levels of heterozygosity and effective population sizes in the Amazonian group in contrast to high levels of linkage and clonality in the Atlantic group. We argue that these differences are linked to strong eco-epidemiological differences between the two regions. In contrast to geographically focused studies, our study provides a broad understanding of the molecular epidemiology of zoonotic parasites circulating in tropical America.